CHANGES IN THE FIELD OF CONTINUOUS EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
The article highlights the priority areas of state policy in the field of education and upbringing of a harmoniously developed generation. About big changes in the field of continuous education, and about further improvement of the system of postgraduate education.